PENGARUH KOMUNIKASI TERHADAP EFEKTIVITAS KERJA PEGAWAI KECAMATAN SUMEDANG SELATAN KABUPATEN SUMEDANG - shofwan Hendryawan; Abdulatif Khoerudin; Andhika Hafid Fauzi; Deva Gilang Pamungkas; Nurlatief Fathurrohman; Riska Putri Septiany (LPPM UNSAP & FISIP UNSAP, 2022)
The purpose of this study was to determine the effect of communication on the work effectiveness of employees at the South Sumedang District Office. This study uses a descriptive analysis method that describes the object of research based on existing and ongoing facts, the process of collecting, compiling and explaining the data obtained and then analyzed with existing theories. The sample is 46 people who are all employees in South Sumedang District. Data collection techniques were carried out using library research and field studies, by means of observation and distributing questionnaires. Data analysis techniques were carried out through instrument validity tests, instrument reliability tests, correlations and percentages, and significant tests. Based on the results of the study, it is known that the communication at the South Sumedang District Service is in good criteria with the results of the analysis reaching 77.33%. Similarly, Employee Work Effectiveness is in good criteria with the results of the analysis reaching 77.46 from the results of the correlation analysis obtained a correlation value of 0.342, which indicates a positive and significant relationship between communication and employee work effectiveness. From the results of the significance test, it is found that the tcount value is greater than t table, namely the t table price (t count price 2.412> 2.015) and the correlation coefficient (r) count of 0.342 which is in the low category. From the analysis of the coefficient of determination, it is known that the communication variable has an influence on Employee Work Effectiveness with 11.69% while the remaining 88.31% is influenced by factors that are not discussed (epsilon) in this study such as the quality factor of Human Resources (HR), Compensation, Leadership, and so on.